2022
DOI: 10.32598/ijpcp.28.1.3697.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Body Image Victimization Experiences and Binge Eating Symptoms: The Mediating Role of Body Image Shame and Self-Criticism

Abstract: Objective: Binge eating disorder is associated with problems in interpersonal and occupational relationships, quality of life, and sometimes weight gain. Many factors affect the formation of these disorder symptoms. The current study examined the relationship between body image victimization experiences and the severity of binge eating symptoms mediated by body image shame and self-criticism. Method: In this study, structural equation modeling was employed. Participants were 283 Iranian university students who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Notably, previous non-network research [ 28 , 70 72 ] suggests that some individuals may engage in ED behaviors and manipulation of shape/weight to cope with shame. However, engaging in ED behaviors to cope with shame may eventually increase shame (e.g., regarding eating, shape and weight), setting up a vicious cycle [ 52 ]. Overall, our findings and those of others suggest that shame may have an important role in initiating ED psychopathology [ 26 , 27 , 29 , 70 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, previous non-network research [ 28 , 70 72 ] suggests that some individuals may engage in ED behaviors and manipulation of shape/weight to cope with shame. However, engaging in ED behaviors to cope with shame may eventually increase shame (e.g., regarding eating, shape and weight), setting up a vicious cycle [ 52 ]. Overall, our findings and those of others suggest that shame may have an important role in initiating ED psychopathology [ 26 , 27 , 29 , 70 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This exposure may increase body dissatisfaction and/or negative affect (e.g., shame, nervousness) when seeing one’s body at home. For example, a recent study indicated that body-related shame was associated with ED psychopathology in Iran [ 52 ]. Of note, bridge symptoms between other psychological constructs (e.g., depression, anxiety) and ED symptoms have differed among individuals in Iran [ 4 , 53 ] compared to those from other countries (e.g..…”
Section: Introductionmentioning
confidence: 99%